1999
DOI: 10.1002/j.2164-490x.1999.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Music Techniques to Treat Adolescent Depression

Abstract: The authors developed a 10‐week school‐based therapy program using music for teenagers who demonstrated depressive symptoms. Pre‐ and posttesting indicated a significant decrease in depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(108 citation statements)
references
References 20 publications
(21 reference statements)
4
98
0
3
Order By: Relevance
“…Adolescents bond with their peers through musical interests and the culture that is generated within musical genres (Hendricks, Robinson, Bradley, & Davis, 1999;Lehtonen & Shaughnessy, 1994). Music stimulates emotions that can foster moments of understanding and break barriers for deeper conversations and meaningful interactions (Lehtonen & Shaughnessy, 1994).…”
Section: Musicmentioning
confidence: 99%
“…Adolescents bond with their peers through musical interests and the culture that is generated within musical genres (Hendricks, Robinson, Bradley, & Davis, 1999;Lehtonen & Shaughnessy, 1994). Music stimulates emotions that can foster moments of understanding and break barriers for deeper conversations and meaningful interactions (Lehtonen & Shaughnessy, 1994).…”
Section: Musicmentioning
confidence: 99%
“…Hendricks et al (1999) conducted a quantitative study with 19 students who showed symptoms of depression. The study was structured as a school-based program that integrated music into group counseling for 14-and 15-year-old students.…”
Section: The Importance Of Implementing Music Interventionsmentioning
confidence: 99%
“…Music interventions provide a way to develop rapport and build a working relationship with students (White, 1985). The school counselor can personalize individual and group counseling interventions to match the unique characteristics of the client, rather than fit the client to a predetermined group of general interventions (Hendricks et al, 1999). School counseling has been shown to improve student behavior and achievement (Bemak, Chi-Ying, & Siroskey-Sabdo, 2005;Brigman & Campbell, 2003;Cook & Kaffenberger, 2003;Lapan, Gysbers, & Petroski, 2001).…”
mentioning
confidence: 99%
“…Le travail peut alors se faire par associations libres sur la musique (Kupperschmitt, 2000), par la relaxation (Davis, & Thaut, 1989;Hendricks, Robinson, Bradley, & Davis, 1999;Lai, 1999;Loveszy, 1996;Robb, 2000;Staum, & Brotons, 2000;Thaut, & Davis, 1993;Waldon, 2001), par des interventions de recadrage (Kerr, Walsh, & Marshall, 2001;Russell, 1992), ou encore par l'imagerie mentale sur la musique (Blake, & Bishop, 1994;Bonde, 1997;Bonny, 1978aBonny, , 1978bBonny, , 1980Bonny, , 1989Bonny, & Savary, 1973;Bruscia, 1996b;Bruscia, & Grocke, 2002;Bums, 2001;Clark, 1996;Hammer, 1996;Jarvis, 1988;Kôrlin, & Wrangsjô, 2001;Kôrlin, & Wrangsjô, 2002;Maack, & Nolan, 1999;McKinney, 1990;McKinney, Antoni, Kumar, Tims, & McCabe, 1997;McKinney, & Tims, 1995;Moffitt, 1996;Nolan, 1983;Pickett, 1996;Rinker, 1996;Russell, 1992;Vaux, 1993).…”
Section: C'est Ainsi Que L'association For Professional Music Therapiunclassified